Impact Response of Composite Sandwich Cylindrical Shells - Reis, Paulo N. B. (2021)
Nowadays, due to the complexity and design of many advanced structures, cylindrical shells are starting to have numerous applications. Therefore, the main goal of this work is to study the effect of thickness and the benefits of a carbon composite sandwich cylindrical shell incorporating a cork core, compared to a conventional carbon composite cylindrical shell, in terms of the static and impact performances. For this purpose, static and impact tests were carried out with the samples freely supported on curved edges, while straight edges were bi-supported. A significant effect of the thickness on static properties and impact performance was observed. Compared to thinner shells, the failure load on the static tests increased by 237.9% and stiffness by 217.2% for thicker shells, while the restored energy obtained from the impact tests abruptly increased due to the collapse that occurred for the thinner ones. Regarding the sandwich shells, the incorporation of a cork core proved to be beneficial because it promoted an increase in the restored energy of around 44.8% relative to the conventional composite shell. Finally, when a carbon skin is replaced by a Kevlar one (hybridization effect), an improvement in the restored energy of about 20.8% was found. Therefore, it is possible to conclude that numerous industrial applications can benefit from cylindrical sandwiches incorporating cork, and their hybridization with Kevlar fibres should be especially considered when they are subject to impact loads. This optimized lay-up is suggested because Kevlar fibres fail through a series of small fibril failures, while carbon fibres exhibit a brittle collapse.